Attitudes and perceptions among urban South Africans towards sugar-sweetened beverages and taxation. Issue 2 (10th June 2019) - Bosire, Edna N; Stacey, Nicholas; Mukoma, Gudani; Tugendhaft, Aviva; Hofman, Karen; Norris, Shane A
Abstract: Objective: A tax on sugar-sweetened beverages (SSB) was introduced in South Africa in April 2018. Our objective was to document perceptions and attitudes among urban South Africans living in Soweto on factors that contribute to their SSB intake and on South Africa's use of a tax to reduce SSB consumption. Design: We conducted six focus group discussions using a semi-structured guide. Setting: The study was conducted in Soweto, Johannesburg, South Africa, 3 months before South Africa's SSB tax was implemented. Participants: Adults aged 18 years or above living in Soweto ( n 57). Results: Participants reported frequent SSB consumption and attributed this to habit, addiction, advertising and wide accessibility of SSB. Most of the participants were not aware of the proposed SSB tax; when made aware of the tax, their responses included both beliefs that it would and would not result in reduced SSB intake. However, participants indicated cynicism with regard to the government's stated motivation in introducing the tax for health rather than revenue reasons. Conclusions: While an SSB tax is a policy tool that could be used with other strategies to reduce people's high level of SSB consumption in Soweto, our findings suggest a need to complement the SSB tax with a multipronged behaviour change strategy. This strategy could include both environmental and individual levers to reduce SSB consumption and its associated risks.